The Influence of Planning, Competence, and Information Technology on Performance in The Faculty of Medicine Hasanuddin University with Organizational Commitment as Moderating Variable - Isdar, Isdar (Scientia integritas Utama, 2022)
This explanatory research was done on purpose to test the hypotheses of the variables of budget planning, human resource competence and also the use of information technology on budget absorption performance, either directly or passing through organizational commitment that becomes the moderating variable. The research was located at the Faculty of Medicine, Hasanuddin University and it has sample of 55 respondents. Data was taken through method of survey by giving set of questionnaires which then calculated using multiple regression and moderated regression analysis. The results shows that budget planning, human resources and information technology have a positive and significant impact toward budget absorption performance. Organizational commitment moderates budget planning.